PENGEMBANGAN APLIKASI DISTRIBUSI PEMBERIAN BANTUAN DALAM RANGKA PEMBERDAYAAN DISABILITAS PADA DINAS SOSIAL MENGGUNAKAN COMPOSER DAN FRAMEWORK LARAVEL - Fitriyani Fitriyani; Desiana Desiana; Husaini Husaini (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2022)
The Regional Social Service Office of Pidie Regency conducted data collection on persons with disabilities with an effort to collec government data on the number of persons with disabilities with the aim of providing assistance to be used to develop various types of businesses with the skills they possess. Data collection for persons with disabilities and disabilities in Pidie District, Pidie District Social Service officers conducted data collection in various villages or sub-districts in each sub-district to obtain accurate data after the data was obtained then the data for persons with disabilities would be reviewed because there are many names that are the same but only thevillages that have disabilities different. the system used by employees for data management for people with disabilities or disabilities still uses a manual system by operating Microsoft Word and Microsoft Excel applications on the windows operating system from the author's observations of the problems that the author finds data input is done one by one according to the author greatly slows down the processing of a data that is very slow. besides that it also takes a very long time. The benefit of research from the Development of Applications for Distribution of Assistance in the Context of Empowering Disability at the Social Service Using Composer and the Laravel Framework is that it is expected to contribute knowledge and useful solutions or alternatives to efforts to improve community services (Distability) that are more competent or structured.Keywords: Application, aid distribution, people with disabilities, framework, Laravel